A comparison between the effectiveness of a gamified approach with the conventional approach in point-of-care ultrasonographic training - Lai, Aaron Kuo Huo; Noor Azhar, Abdul Muhaimin bin; Bustam, Aidawati binti; Tiong, Xun Ting; Chan, Hiang Chuan; Ahmad, Rashidi; Chew, Keng Sheng (Springer Nature, 2020)
Background